The Concept of Lesbian, Gay, Bisexual and Transgender (LGBT) is seen from the Legal Norms of Indian Society - Hasby Matlul Samaha (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2023)
This research is to find out that most homosexuals (Lesbian, Gay and transgender) begin to realize that they have different tendencies at a young age. Studies show that homosexual behavior and same-sex attraction are common from the age of 15, the prevalence is in men, in America 20.8%, UK 16.3%, and America 18.5%. While in the women's group respectively 17.8%, 18.6%, and 18.5%. This situation shows that the school age group is a vulnerable age to start engaging in same-sex relationships. This study uses cross-sectional (cross-sectional) with a qualitative approach. Data was collected using in-depth interviews, focus group discussions and literature review. While the decision to become homosexual mostly occurs at the age of young adults or at the age when most of them are students. Becoming LGBT is not an easy endeavor and even afterwards it is not without problems, many problems and risks arise when young adolescents start to engage in same-sex relationships, for young men the lack of knowledge about the risks of sexual relations can cause them to be easily exposed to HIV and sexual harassment from those with more experience . Ignorance of their state of self can also lead to social turmoil and depression. For young men, the lack of knowledge about the risks of having sex can make them more susceptible to HIV exposure and sexual harassment from those with more experience. Ignorance of their state of self can also lead to social turmoil and depression. For young men, the lack of knowledge about the risks of having sex can make them more susceptible to HIV exposure and sexual harassment from those with more experience. Ignorance of their state of self can also lead to social turmoil and depression.